Points of contact or friction? Documents of national defense from Brazil and from United States - Svartman, Eduardo (Conjuntura Austral, 2012)
This paper investigates the topics that reveal disagreements and convergences in defense and international security policies in Brazil and the United States. Assessing the chances of friction between the two countries, one argues that the documents which makes public both countries strategies reveal important changes in the guidelines issued by each country to the other and that, despite ambiguities and mismatches, since 2010, there is more discursive space from U.S. to Brazil set agenda and negotiate his strategic interests.